Formulation And Evaluation Of Metformin Hydrochloride Sustained Release Capsule - R, Joan Vijetha; K, Kaviyarasan; A, Annie Bhuvana Mary; N, Gopinath; J, Sam Daniel (Journal of Neonatal Surgery, 2025)
Metformin Hydrochloride (MH) is a synthesis of N, N -dimethyl guanidine, a type of medicament which is used to treat type II diabetes. Emil Worner and James Belt in the year 1922 were the first to synthesized dimethyl guanidine. MH has various other advantages such as; weight loss, improper fertility, slowing down the tumour growth and few more. The current work is focused on, to sustain the release of the drug in the body for a larger period of time. To perform this study various factor were taken into consideration such as drug, Excipients (HPMC, PVP K30, Magnesium stearate, MCC, NaCMC and Starch) compatibility study, Preformulation studies of raw material and granules. The granules were prepared using wet granulation method, and all the quality control parameter study for formulated 10 capsules were performed. Out of these 10 formulations, formulation 7 (F7) was subjected to have sustain release. Further, F7 was subjected to comparative study with other marketed available tablet and was found out that our formulation has sustained release up to the 13th hr and were as marketed tablet up to 11th hr. Finally accelerated stability study was performed till 3 months and was found that there were no significant changes.